Optimizing the performance of ontological knowledge bases built on the basis of «VIRTUOSO» - Бибичков, Игорь Евгеньевич; Сокол, Вадим Викторович; Шевченко, Александр Юрьевич (Eastern-European Journal of Enterprise Technologies, 2014)
This work contains a research of available methods on query optimization of OWL knowledge bases that are built using the SPARQL language, and also by using the available frameworks (e.g. Apache Jena Framework). Currently, there is a special need to improve the performance of existing tools to work with knowledge bases. This need is caused by a lack of the speed, and sometimes, by a very low performance of systems that uses a knowledge bases as a data storage. As a result of the research it was found an opportunity of significant performance optimization of interactions with knowledge bases, based on Virtuoso server, by applying the described optimization techniques that resulted in an increase in execution speed, in average from 25% to 35%, with a relatively small number of triplets. This information will help developers to reduce the time of interaction with knowledge base server that will significantly speed up the performance of applications that use similar data storage.